2023
DOI: 10.1021/acsami.3c06424
|View full text |Cite
|
Sign up to set email alerts
|

Main-Chain Cationic Bile Acid Polymers Mimicking Facially Amphiphilic Antimicrobial Peptides

Abstract: Antibiotic-resistant bacterial infections have led to an increased demand for antibacterial agents that do not contribute to antimicrobial resistance. Antimicrobial peptides (AMPs) with the facially amphiphilic structures have demonstrated remarkable effectiveness, including the ability to suppress antibiotic resistance during bacterial treatment. Herein, inspired by the facially amphiphilic structure of AMPs, the facially amphiphilic skeletons of bile acids (BAs) are utilized as building blocks to create a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Their systematic exploration demonstrated that MCBAP with amphiphilic structure displayed an effective activity against Gram-positive methicillin-resistant Staphylococcus aureus and Gram-negative Escherichia coli, fast killing efficacy, superior bactericidal stability in vitro, and potent anti-infection. [38] Upon adsorption onto the bacterial membrane surface, antibacterial polymers initiate interactions with microorganisms through their hydrophobic segments, leading to the disruption of membrane integrity. The nature of these hydrophobic segments, including their category, length, and position, has been reported to exert a significant impact on the bactericidal efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their systematic exploration demonstrated that MCBAP with amphiphilic structure displayed an effective activity against Gram-positive methicillin-resistant Staphylococcus aureus and Gram-negative Escherichia coli, fast killing efficacy, superior bactericidal stability in vitro, and potent anti-infection. [38] Upon adsorption onto the bacterial membrane surface, antibacterial polymers initiate interactions with microorganisms through their hydrophobic segments, leading to the disruption of membrane integrity. The nature of these hydrophobic segments, including their category, length, and position, has been reported to exert a significant impact on the bactericidal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Their systematic exploration demonstrated that MCBAP with amphiphilic structure displayed an effective activity against Gram‐positive methicillin‐resistant Staphylococcus aureus and Gram‐negative Escherichia coli , fast killing efficacy, superior bactericidal stability in vitro, and potent anti‐infection. [ 38 ]…”
Section: Introductionmentioning
confidence: 99%